Fuzzy-based Prioritization of Health, Safety, and Environmental Risks: The Case of a Large Gas Refinery - Auob Mirsaeidi; Hossein Moradi; Maryam Zekri (Iranian Journal of Health, Safety and Environment, 2017)
The main objective of this study was to develop a fuzzy-based framework for the prioritization of health, safety and environment related risks posed against employees, working conditions, and process equipment in large gas refineries. The First Refinery at Pars Special Economic Energy Zone in South of Iran was taken as a case study. For this purpose, health, safety and environment related risks were determined based on the three criteria of impact severity, occurrence probability, and detect-ability using a questionnaire of 33 identified failures. The values obtained were processed by a so-called 'contribution coefficient'. The results were then subjected to fuzzification and fuzzy rules were defined to calculate the risk level indices as the model outputs, which was then employed to facilitate the management decision-making process by prioritizing the management options. The prioritization values were then classified in six categories in the order of risk severity. Results revealed that failure in a combustion furnace had the highest rank while failure in the slug catcher ranked the lowest among the risk sources. It was also found that about 0.4% of the identified risks prioritized as "intolerable", 79% as "major", 20% as "tolerable", and 0.7% as "minor". Thus, most of the risks (more than 79%) associated with the refinery has the potential of significant risks. The results indicated that the risk of the pollutant emissions from the combustion furnaces is the highest. Exposures to harmful physical, chemical, psychological, and ergonomic substances are the other risks, respectively.